More Pivots than a Centipede on Ice Skates: Reflections on Shared Leadership in a Post-Secondary Institution During COVID-19 - Smith, Dan (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation)

(untitled) (Department of Educational Administration, University of Saskatchewan, 2022)
This article is a case study describing the University College of the North’s (UCN) response to the COVID-19 pandemic, outlining pandemic planning and management processes at UCN from March 11, 2020, to September 30, 2021. UCN’s planning processes evolved from a top-down approach led by administration to an approach that saw greater shared leadership in the crisis. Shared leadership included senior leaders, middle management, faculty, and staff who both addressed the immediate crisis and engaged in post-pandemic planning. Lessons learned may help post-secondary institutions gain greater resiliency and sustainability as the post-COVID environment emerges.